Conglomerados financeiros: análise de seu desempenho no Brasil, no período de 1978/1981 - Perdigão, Luís Antonio (1983)
This work is the result of a field research carried out during the year of 1990 in Porto Velho - RO, with the assistence of agricultral experts and use secondary sources of information, aiming to get acquainted with Public Policy for agriculture in the state, to identify and to analyse the result of those policies and present suggestions for chenges considering the migration. The study describes and analyses the State Public Policies, presenting a historical vision of its economical farmation by reconstituting its past, fron the extractivistic stages and the present days. The economic evolution of Rondonis was analysed, and fact that the influence of the economic and social facts upon the migratory flows toward Porto Velho has been raising, proportionally from the very beginning of its history until the present days becarnse notorious. Problems resulting from the increasing urbanization of the cities, specially affected by the migration process of the rural population, and population' s troubles caused by the insuitable agricultural Policy has also been approached. I carne to the conclusion that the State Policy for agriculture IS not appropriate due to several reasons, which wiIl be pointed out in this work. Finally, suggestions are given to reformulate the State Policy for agriculture, to overcome some of the great problems concerning this matter which affects mainly the migrating population that come from rural areas to the urban surroundings.